Mindfulness for anxious kids : a workbook to help children cope with anxiety, stress, and worry - Cook-Cottone, Catherine; Vujnovic, Rebecca K (Oakland, CA : Instant Help Books, an imprint of New Harbinger Publications, Inc., 2018)
Between school, friends, and just growing up, it's normal for kids to feel worried or anxious some of the time. But if your child's anxiety is getting in the way of achieving goals or living life, they may need a little extra help managing stress and difficult feelings. This workbook is a great place to start. The Mindfulness Workbook for Anxious Kids provides engaging and evidence-based activities grounded in mindfulness practices and dialectical behavior therapy (DBT) to help kids stay calm and balance their emotions--whether they're at school, with friends, or at home. Using the skills outlined in this workbook, your child will learn to manage anxiety associated with daily life, anxiety disorders, and trauma. The workbook also addresses specific anxiety issues, such as panic, separation anxiety, social anxiety, and phobias. Emotions can be confusing, and negative or difficult emotions are often the cause of anxiety in children. But emotions cannot be avoided. This workbook will help your child make friends with their emotions, understand them, and use them effectively.
"30 simple, fun activies to help kids: work through big feelings ; feel calm at home & school ; be kind to themselves & others"--Cover.
Keywords: Mind and body -- Juvenile literature; Self-consciousness (Awareness) -- Juvenile literature; Self-help techniques -- Juvenile literature; Meditations for children; Awareness -- Juvenile literature